Glacier velocities and dynamic ice discharge from the Queen Elizabeth Islands, Nunavut, Canada. Issue 2 (23rd January 2014) - Van Wychen, Wesley; Burgess, David O.; Gray, Laurence; Copland, Luke; Sharp, Martin; Dowdeswell, Julian A.; Benham, Toby J.
Abstract Recent studies indicate an increase in glacier mass loss from the Canadian Arctic Archipelago as a result of warmer summer air temperatures. However, no complete assessment of dynamic ice discharge from this region exists. We present the first complete surface velocity mapping of all ice masses in the Queen Elizabeth Islands and show that these ice masses discharged ~2.6 ± 0.8 Gt a−1 of ice to the oceans in winter 2012. Approximately 50% of the dynamic discharge was channeled through non surge‐type Trinity and Wykeham Glaciers alone. Dynamic discharge of the surge‐type Mittie Glacier varied from 0.90 ± 0.09 Gt a−1 during its 2003 surge to 0.02 ± 0.02 Gt a−1 during quiescence in 2012, highlighting the importance of surge‐type glaciers for interannual variability in regional mass loss. Queen Elizabeth Islands glaciers currently account for ~7.5% of reported dynamic discharge from Arctic ice masses outside Greenland.